Sentinel lymph nodes with isolated tumour cells and micrometastases in breast cancer: clinical relevance and prognostic significance. Issue 3 (11th November 2013) - Ahmed, Syed Salahuddin; Thike, Aye Aye; Iqbal, Jabed; Yong, Wei Sean; Tan, Benita; Madhukumar, Preetha; Ong, Kong Wee; Ho, Gay Hui; Wong, Chow Yin; Tan, Puay Hoon
Abstract : Aim: We performed a retrospective review to determine the prognostic significance of isolated tumour cells (ITCs) and micrometastases to the sentinel lymph nodes of patients with breast cancer. Methods: A total of 1044 patients with a diagnosis of invasive carcinoma of the breast who underwent surgical treatment including the sentinel lymph node biopsy procedure from July 2004 to October 2009 were included in the study. Results: In 710 (68%) patients, no metastasis was seen to the sentinel lymph nodes. ITCs were detected in 22 (2.1%) patients, micrometastasis in 52 (5.0%) and macrometastases in 260 (24.9%). With a median follow-up of 28.8 months, disease recurrence was seen in 38 (3.6%) patients and 15 (1.5%) patients died of disease. No disease recurrence or deaths were recorded in women with ITCs in sentinel lymph nodes. In the micrometastasis group, 2 patients suffered disease recurrence and both died of disease. Conclusions: We conclude that ITCs in the sentinel lymph nodes did not adversely impact disease free and overall survivals. Although only 2 recurrences with subsequent death occurred in the micrometastasis group, it may suggest a propensity for presence of micrometastases to augur a worse outcome, and justifies continued segregation of ITCs from micrometastasis.